2016
DOI: 10.1038/srep34182
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity and gender differences induced by cadmium telluride quantum dots in an invertebrate model organism

Abstract: Sexual glands are key sites affected by nanotoxicity, but there is no sensitive assay for measuring reproductive toxicity in animals. The aim of this study was to investigate the toxic effects of cadmium telluride quantum dots (CdTe-QDs) on gonads in a model organism, Bombyx mori. After dorsal vein injection of 0.32 nmol of CdTe-QDs per individual, the QDs passed through the outer membranes of gonads via the generation of ROS in the membranes of spermatocysts and ovarioles, as well as internal germ cells, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The genetic integrity of the gonads is an essential aspect of reproductive success [63]. Thus, as ROS can harm the DNA and cells, this damaged genetic will be inherited to the next generation as the defective genetic [64,65]. In summary, even though the direct evidence that the PS-NPs passed through the bio-barrier and moved to further tissues in fish, such as gonads and brain, could not be shown; the fact that these organs were affected become an indicator from the perspective of biological effects.…”
Section: Reproductive Toxicity Of Ps-npsmentioning
confidence: 99%
“…The genetic integrity of the gonads is an essential aspect of reproductive success [63]. Thus, as ROS can harm the DNA and cells, this damaged genetic will be inherited to the next generation as the defective genetic [64,65]. In summary, even though the direct evidence that the PS-NPs passed through the bio-barrier and moved to further tissues in fish, such as gonads and brain, could not be shown; the fact that these organs were affected become an indicator from the perspective of biological effects.…”
Section: Reproductive Toxicity Of Ps-npsmentioning
confidence: 99%
“…, amide; NM, nanomaterial; NOS, nitric oxide synthase; NeUT, neutrophilic granulocyte count; NP, nanoparticle; nSPs, nanosilica particles; PbS, lead sulfide; PEG-b-PLA, poly(ethylene glycol)-block-poly(d,l-lactic acid); PI, propidium iodide; P4, progesterone; PND, postnatal day; QD, quantum dot; RBC, red blood cell;RIA, radioimmunoassay; RT-PCR, real-time PCR; SD, Sprague Dawley; SOD, superoxide dismutase; SeM, scanning electron microscope; SLGO, single-layer graphene oxide; SSCs, spermatogonial stem cells; tPA, tissue plasminogen activator;T, testosterone; TeM, transmission electron microscopy; wBC, white blood cells; vCL, curvilinear velocity; vSL, straight line velocity.of spermatocysts and ovarioles and in internal germ cells, leading to the induction of early germ cell death or malformations via complex mechanisms related to apoptosis and autophagy through mitochondrial and lysosomal pathways 72. AgNPs cause apoptosis, necrosis, and decreased proliferation and an increase in DNA strand breaks in NT2 cells 73.…”
mentioning
confidence: 99%
“…The accumulation of QDs in testicular tissue indicated that there was an interaction between QDs and biological barrier, leading to the uptake and distribution of QDs [19]. Yan et al CdTe QDs could pass through the outer membrane of the silkworm's gonad, produce reactive oxygen species (ROS) in membranes of spermatocysts and internal germ cells, and affect the reproductive system [20]. Zhao et al found that the uorescent NPs derived from roasted pork could distribute rapidly in the testis of mice within 24 hours after oral administration [21].…”
Section: Biodistribution Of Cdse/zns Qds In Testesmentioning
confidence: 99%